3D hydrodynamics simulations of massive stars with the PROMPI code. Issue 1 (1st March 2022) - Rizzuti, F; Hirschi, R; Georgy, C; Arnett, W D; Meakin, C; Mocák, M
Abstract: Evolutionary models of massive stars are affected by uncertainties related to three-dimensional processes like convection. However, it is not computationally possible to simulate at the same time both the entire lifetime of a star and its fluid motions. 3D hydrodynamics simulations can be employed to study the fluid behaviour in very high detail for a short time-scale, which can be used to improve 1D models. The code PROMPI is a multi-dimensional hydrodynamics software developed specifically for simulations of the late phases in massive star interiors. In these proceedings, we present results from a new PROMPI simulation of the neon-burning shell in a 15 M© star, focusing on the interplay between convective turbulence and nuclear reactions. In particular, we show how it is possible to use the chemical composition to study the time evolution of the convective zone, which is subjected to turbulent entrainment.